2021
DOI: 10.1186/s41936-021-00214-1
|View full text |Cite
|
Sign up to set email alerts
|

The toxic effect of zinc oxide nanoparticles on the terrestrial slug Lehmannia nyctelia (Gastropoda-Limacidae)

Abstract: Background Chemicals have deleterious effect on the environment. The wide use of nanomaterials as products for plant protection, fertilizers, and also in water purification leads to the release of these materials to the environment. Terrestrial gastropods including snails and slugs have the ability to accumulate heavy metals in their bodies. The present study evaluates the toxic effect of zinc oxide nanoparticles on the terrestrial slug Lehmannia nyctelia. Zinc oxide nanoparticles (ZnO NPs) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Ag ions taken up by water and/or transdermal could have been internalized more easily than Ag 2 S NPs, since Ag ions can enter cells via ion transport channels (e.g., proton-coupled Na + channels) while Ag particles may be too large (Khan et al, 2015). Uptake of metals bound to particulate material has been suggested to mainly occur in the digestive gland of molluscs (Kuehr et al, 2021;Marigómez et al, 2002;Mohammad et al, 2021), which was the major target tissue for Ag accumulation in freshwater snails (Bao et al, 2018). Once contaminated food reached the digestive gland, different processes may occur, such as endocytosis or phagocytosis in digestive cells, potentially leading to different elimination of ionic and nanoparticulate Ag.…”
Section: Discussionmentioning
confidence: 99%
“…Ag ions taken up by water and/or transdermal could have been internalized more easily than Ag 2 S NPs, since Ag ions can enter cells via ion transport channels (e.g., proton-coupled Na + channels) while Ag particles may be too large (Khan et al, 2015). Uptake of metals bound to particulate material has been suggested to mainly occur in the digestive gland of molluscs (Kuehr et al, 2021;Marigómez et al, 2002;Mohammad et al, 2021), which was the major target tissue for Ag accumulation in freshwater snails (Bao et al, 2018). Once contaminated food reached the digestive gland, different processes may occur, such as endocytosis or phagocytosis in digestive cells, potentially leading to different elimination of ionic and nanoparticulate Ag.…”
Section: Discussionmentioning
confidence: 99%
“…alexandrina snails, where degeneration of secretory cells was obvious. Additionally, Mohammad et al (2021) demonstrated histopathological alterations in the digestive gland of the gastropod slug; Lehmannia nyctelia exposed to ZnO nanoparticles for 10 days, as vacuolation, shrinkage and rupture of cells took place. It was claimed that when nanoparticles are ingested by an organism, they may get stuck in the digestive tract and not absorbed, yet induce a series of physiological changes that harm the organism, such as a decrease in the absorption of nutrients (Bour et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the gonads of L. nyctelia slug were negatively affected after treatment with ZnO nanoparticles. These effects include disruption of oocytes, aggregation of early gametogenic stages and emptiness of acini (Mohammad et al, 2021). that ZnONPs possibly have the potential to damage DNA.…”
Section: Genotoxic Effectmentioning
confidence: 99%
“…release amino cyclopropane (1-carboxylic acid (ACC)) deaminase and bioactive metabolites (surfactant and lipopeptides) that covered the seed toxicity [33]. Furthermore, Zn +2 ions are essential for bacterial enzymes (dehydrogenase, thiol peroxidase, and glutathione reductase) that enhanced the growth by uptake of nutrient reserves and metabolic and antioxidative activities [34]. Zinc ions also increased the cell stability by the nutrition uptake, water molecules, and translocation in plant tissues and enhanced the resistance level of plant against toxicity [35].…”
Section: Discussionmentioning
confidence: 99%